Snail‐mediated cancer stem cell‐like phenotype in human CNE2 nasopharyngeal carcinoma cell. Issue 3 (12th October 2017) - Peng, Shan; Wu, Cheng; Sun, Wei; Liu, Dongbo; Luo, Min; Su, Beibei; Zhang, Linli; Mei, Qi; Hu, Guoqing
Abstract: Background: Cancer stem cell (CSC)‐like phenotype, which has been proven to play a critical role in invasion and metastasis of many kinds of cancers, has also been reported to be associated with epithelial‐mesenchymal transition. Snail, a potent repressor of E‐cadherin expression, was found to have a function to regulate the aforementioned processes. Methods: In the current study, expression of putative CSCs biomarkers and the ratio of CSC‐like CNE2 (cancer cell line) in total CNE2 were measured, and CSC‐like characteristics were analyzed with tumor‐sphere self‐renewal and colony‐forming assays. Migration and invasion properties were determined by using transwell and wound healing assays. Xenograft tumor assays in vivo were done to evaluate the function of Snail and radiation in the tumor forming ability. Results: In human nasopharyngeal carcinoma (NPC) cells, overexpression of Snail mediates a CSC‐like phenotype, which enhances the initiation, invasion, and migration ability of cancer cells. Conclusion: Thus, Snail is a potential therapeutic target in NPC.